A review of thermal history and timescales of tectonometamorphic processes in Sikkim Himalaya (NE India) and implications for rates of metamorphic processes. (23rd June 2016) - Chakraborty, S.; Anczkiewicz, R.; Gaidies, F.; Rubatto, D.; Sorcar, N.; Faak, K.; Mukhopadhyay, D.K.; Dasgupta, S.
Abstract: The lesser and greater Himalayan sequences (LH and GH) in Sikkim have been studied in detail recently. The LH consists mainly of pelitic lithologies with detrital zircon ages >1800 Ma and ε Nd (0) of −27.7 to −23.4 (with intercalated calcsilicates, metabasites and a sheared granite gneiss – the Lingtse gneiss). The metamorphic sequence is characterized by (i) a remarkably continuous and systematic metamorphic field gradient (~60–70 °C kbar −1 ), (ii) peak pressures as well as temperatures of metamorphism increasing at higher metamorphic grades (~5 kbar, 500 °C at the garnet zone to ~8 kbar, 700 °C at the sillimanite–muscovite‐zone), (iii) clockwise P – T paths of a tight 'hairpin' shape with a prograde slope of 20–30°C kbar −1, (iv) initiation of garnet growth (Lu–Hf chronometry) at systematically older ages at higher grades (11–10.5 Ma at garnet zone to 16.8 Ma at sillimanite–K‐feldspar zone), (v) peak of metamorphism simultaneously at all grades (13–11 Ma), (vi) deformed and folded metapelitic rocks but with little evidence of pervasive shearing and (vii) duration of melt formation and segregation on the order of a few 100, 000 years. The degree of melting was low, as indicated by the presence of muscovite all through the sequence. This evidence indicates that the LH behaved as a coherent block, and thermomechanical models quantitatively reproduce many of these features as well as explain the formation of inverted metamorphic sequence in such a coherent block. The greater Himalayan sequence (GH), also largely metapelitic, has different protoliths (with components as young as 800 Ma) and a different metamorphic history (extensive migmatization at higher grades ~8–12 kbar, 750–850 °C at an older age of largely >20 Ma along a different clockwise P – T path characterized by sharp, isothermal decompression followed by near isobaric cooling). Geochronological data (monazite, zircon, garnet) as well as cooling rate calculations (geospeedometry) reveal that the GH is made up of at least two blocks with distinct, complex and multistage P – T – t histories. Different stages of the high‐ T cooling were rapid (100's °C Ma −1 to 10's °C Ma −1 at different stages) and at least some of it was unrelated to exhumation; synthesis of these results with low‐ T thermochronometry allows the detailed multistage cooling and exhumation history of this block to be reconstructed. The reconstructed cooling and exhumation histories show that a number of interlinked processes operating on a hierarchy of timescales leads to the overall evolution. The P – T history with rapid cooling can be reproduced by thermomechanical models that consider conductive as well as advective heat transport and there is no need to invoke additional processes (such as the role of fluids). Metabasic inclusions within both the LH and the GH appear to record a different (? older in part) history. The role of these in the overall evolution, as well as the difference in metamorphic ages of the LH and GH remain open questions that need to be addressed in future research.